The earliest Yoruba translation of the Qur'an: missionary engagement with Islam in Yorubaland - Solihu, Abdul Kabir Hussain (Edinburgh University Press, 2015)
This study analyses the first translation of the meaning of the Qur'an into Yoruba, a language spoken mainly in south-western Nigeria in West Africa. Yorubaland in the nineteenth and twentieth centuries was a theatre of serious engagement between Muslims and Christian missionaries, during which a proliferation of translations of religious texts played a major role. Long before the translation of the Qur'an was accepted by most Muslims in Africa, Christian missionaries had taken the initiative in rendering the Qur'an into local African languages. The first known translation of the Qur'an into any African language was Reverend M.S. Cole's Yoruba translation, which was first published in 1906, and republished in 1924 in Lagos, Nigeria. This ground breaking work, written primarily for a Christian audience, was not widely circulated among Yoruba scholarly circles and thus did not generate significant scholarly discourse, either at the time or since. This study, which is primarily based on the 1924 edition of Reverend Cole's translation, but also takes into account other materials dealing with the Muslim-Christian engagement in the nineteenth and early twentieth centuries in Yorubaland, examines the historical background, motives, and semantic structure of the earliest Christian missionary-translated Yoruba Qur'an.